Peramalan Inflasi Kota Balikpapan Menggunakan Metode Singular Spectrum Analysis - Sergio, Andrean; Wahyuningsih, Sri; Siringoringo, Meiliyani (Program Studi Statistika FMIPA Universitas Mulawarman, 2023)
Singular Spectrum Analysis (SSA) is a nonparametric forecasting method capable of separating time series data into interpretable trend, seasonal, cycle, and noise. Methods with component separation are suitable for characterizing economic and business data trends that tend to contain stationary, trend, cycle, and seasonal factors. One of the economic data that can be used in research is inflation. The purpose of this study is to obtain the results of inflation forecast in Balikpapan City from November 2022 to October 2023. Based on the forecasting results of the SSA method on inflation in Balikpapan City, the MAAPE value was 23.53% which showed that the forecasting results were quite accurate. Based on the results of inflation forecast from November 2022 to October 2023, there was a decrease in inflation in November 2022 by -0.64% or it could be said that there would be deflation by 0.64%. Over the next period, inflation tends to increase where the highest inflation will occur in June 2023, which is 1.96%.